Del sentido de la muerte en Paul Ricoeur - Castellanos Rodríguez, Belén (Nómadas. Critical Journal of Social and Juridical Science, 2015)
Based on the work of Paul Ricoeur, the following article presents a non- humanist reformulation of the question of the meaning of life, with which to come out of nihilism and the idea that humans can, happily, drop out this question and welcome without more, to the affirmation of chaos or manufacture of merely subjective or gregarious or provisional senses. The need to rescue the role of faith, fate and sacrificial love is show, shifting the question of the meaning of life the question to the meaning of death which, if achieved rebellious and significant, will be placed in response and finishing hermeneutic act.